(untitled) (Fiep Bulletin - online, 2016)
The Depression and its variations are considered to be the "evil of the century" with some of the most common vices presented in individuals with depression is alcoholism and smoking. Objective: To investigate the correlation between depression and consumption of illicit drugs. Methodology: The study is conducted descriptive epidemiological type, cross-sectional, quantitative; whose sample consisted of 104 individuals who agreed to participate in the survey by answering a form containing objective questions that were used as variables. The data, compiled after, were presented in tables and graphs simple frequency expressed in numbers and percentages. Ethical aspects were respected, according to Resolution No. 196/96 (CNS-MS). Results: 4.8% of respondents have relationship of depression with use of illicit drugs, 29.78% men and 14.03% women have a tendency to alcoholism; 8.51% of men and 17.54% of women have a high level of smoking; 47.21% of the research subjects tends to depression 20,19% make moderate use of alcohol and cigarettes. The results suggest that individuals with high levels of smoking have a predisposition to depression, while people prone to alcoholism has a lower propensity to disease. Other factors such as bereavement, illness and poor quality of life are extremely important to generate this disorder being associated with moderate or abuse of drugs.